CARDIOVASCULAR DISEASES: PROFILE OF MALE WORKERS FROM A DISTILLERY IN THE COUNTRYSIDE OF SÃO PAULO STATE - Miyeko Hayashida; Evandro José Cesarino; Maria Suely Nogueira; Manuel Simão (Universidade Federal de Goias, 2002)
The study presents the profile of 123 workers from a distillery, with regard to the risk factors ofcardiovascular diseases. The results disclose 10,6% of the workers with level-1 obesity, 17,0% had level-2 obesity,11,4% with systolic arterial pressure values 140 mmHg, 12,2% with diastolic arterial pressure values 90 mmHg,60,2% had incomplete elementary school education, 40,7% reported the habit to perform physical activity, 16,3%were smokers, 65,9% indicated the consumption of alcoholic beverages and 49,6% reported to ingest salt inexcess. Concerning their family history, 32,5% reported a family history with the pressure of hypertensive disease,26,0% for cerebral vascular accidents and 27,6% for diabetes mellitus.